Sea level characteristics in Puerto Quequén - Piccolo, María Cintia (1997)
Sea level observations at the mouth of the Quequén Grande river, Puerto Quequén station, are used to study the sea level variation in different time scales: tidal and subtidal fluctuations, sea level variation and seiches in the estuary. Four tidal constituents are found to be the most active in Puerto Quequén, with M2 being the most important. At subtidal frequencies, the sea level variations are primarily forced by atmospheric forcing on the adjacent shelf. Spectral analysis evidenced atmospheric forcing into the estuary at macro, synoptic and local scale.